Optimalisasi Pelayanan Keperawatan Jiwa Di Panti Rehabilitasi Nyaman Jiwo Basung Pancuranmas Secang Magelang - Muhammad Khoirul Amin; Noviyana Pujihastusi; Apridira Diar Nugrahani; Esti Ria Aigustina; Mardiyana Agustina (STMIK Royal, 2022)
Abstract: Based on a preliminary survey with the owner of the rehab, it was found that the Nyaman Jiwo Rehab has a total of 35 patients being treated, 6 nurses who take care of patients with mental disorders every day. The owner of the rehab stated that the foundation already has a concept plan for developing vocational therapy skills including making agricultural land (vegetables, secondary crop), animal husbandry (cows, goats, ducks), sewing skills and cooking/cooking skills. It is hoped that through the rehabilitation services at the Nyaman Jiwo Rehab, the patient will be able to be independent